(untitled) (Research, Society and Development, 2022)
Introduction: In recent years there has been a considerable increase in the use of plastic products for different purposes. Many of the plastics generated are dumped into the environment inappropriately. Therefore, it is possible to find plastic waste in different ecosystems, with the marine environment being one of the most impacted. The objective of this review is to identify the impacts of microplastics on the environment and their impact on human health. Methodology: This work corresponds to a narrative literature review, using articles published from 2017 to 2022. The search for articles was carried out in the following databases: Sciencedirect, Scholar Google and Springer-Verlag, using the descriptors: microplastics, plastic pollution and environmental impact. Result: Plastics discarded in the environment go through different processes, such as environmental and biological stresses synergistically which allow these plastics to be broken down into particles smaller than 5 mm called microplastics. The current scenario of microplastic pollution is in evidence and has been causing concern to researchers around the world, since these pollutants are complex contaminants and have significant toxic effects. Current research proves that prolonged exposure to these particles jeopardizes the survival of marine life and induces serious damage to human health, since they can cause damage to the cell and its genetic material, in addition to providing a surface for the transport of microorganisms. And other chemical compounds. Conclusion: Studies show that microplastics pose potential risks to the marine environment and threaten human health, requiring urgent action to recover and avoid environmental impacts.